2013
DOI: 10.3725/jjn.43.21
|View full text |Cite
|
Sign up to set email alerts
|

Development of a direct quantitative detection method for Meloidogyne incognita and M. hapla in andosol and analysis of relationship between the initial population of Meloidogyne spp. and yield of eggplant in an andosol

Abstract: Baermann method, while that of M. incognita and M. hapla from 0.6 to 713 J2 equivalent (J2eq)/20 g soil and from 0.0 to 115 J2eq/20 g soil, respectively, with the real-time PCR method. The yield was determined by the sum of commercial sized eggplants harvested for 3 months of the cultivation period. The yield decreased in the plots with an initial population of RKNs more than 2 J2/20 g soil with the Baermann method. In real-time PCR, the yields were low in the plots with the sum of initial M. incognita and M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…in the tropics (Sasser, 1979). Recently, Watanabe et al (2013) reported that the yield of eggplant was decreased by an initial population of Meloidogyne spp. consisting of more than two-second-stage juveniles per 20 g soil.…”
Section: Introductionmentioning
confidence: 99%
“…in the tropics (Sasser, 1979). Recently, Watanabe et al (2013) reported that the yield of eggplant was decreased by an initial population of Meloidogyne spp. consisting of more than two-second-stage juveniles per 20 g soil.…”
Section: Introductionmentioning
confidence: 99%
“…(M. incognita is dominant) in the tropics (Sasser, 1979) and the economic threshold level of eggplant is reported to be 5.4 M. incognita second-stage juveniles (J2) per 100 g soil (Netcher and Sikora, 1990). Recently, Watanabe et al (2013) reported that soil densities of two J2 per 20 g soil or greater with the Baermann technique have been shown to significantly reduce eggplant yield (cultivar Senryo 2go) at 50 days after planting.…”
Section: Introductionmentioning
confidence: 99%
“…(M. incognita is dominant) in the tropics (Sasser, 1979) and the economic threshold level of eggplant is reported to be 5.4 M. incognita second-stage juveniles (J2) per 100 g soil (Netcher and Sikora, 1990). Recently, Watanabe et al (2013) reported that soil densities of two J2 per 20 g soil or greater with the Baermann technique have been shown to significantly reduce eggplant yield (cultivar Senryo 2go) at 50 days after planting.Most plant nematode control methods rely on chemical agents. Although soil fumigants such as 1,3-dichloropropene are commonly used, the use of such chemicals is likely to be subject to increasing restriction owing to environmental and safety concerns.…”
mentioning
confidence: 99%
“…Density of plant parasitic nematodes is measured with real-time PCR and relations between densities and damage to crops have been evaluated e.g. in Pratylenchus penetrans (Cobb) Filipjev and Schuurmans Stekhoven against radish , M. incognita against eggplant (Watanabe et al, 2013) and Hirschmanniella diversa Sher against lotus (Koyama et al, 2013). However, the relationship between the density of M. incognita and damage to tomato is not yet established.…”
Section: Soil Samplingmentioning
confidence: 99%
“…Watanabe et al (2013) reported that eggplant' s yield losses were observed in plots with an initial population of M. incognita and M. hapla Chitwood more than 128 J2eq/20 g soil measured with real-time PCR.…”
Section: Literature Citedmentioning
confidence: 99%